2019
DOI: 10.22454/fammed.2019.477798
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Student-Run Clinic on Emergency Department Utilization

Abstract: Background and Objectives: Student-run clinics (SRCs) provide primary care access to low-income patients who would otherwise pursue more expensive care, such as visits to emergency departments (ED). Decreasing inappropriate ED utilization offers an opportunity to create value in the health care system. However, to date, no SRC has rigorously studied this. This study examines whether increased access to ambulatory care through an SRC, the Crimson Care Collaborative (CCC), is associated with decreased ED utiliza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 3 publications
0
19
0
Order By: Relevance
“…Previous studies investigating the impact of UCS have reported substantial reductions in "avoidable" ED visits, as well as cost reductions [11][12][13][14][15]. Using a questionnaire, Moe et al measured the impact of an after-hours clinic in terms of avoided ED visits and cost savings, and found that 36.8% of patients attending the after-hours clinic would otherwise have gone to the ED if the clinic had not been available [11].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies investigating the impact of UCS have reported substantial reductions in "avoidable" ED visits, as well as cost reductions [11][12][13][14][15]. Using a questionnaire, Moe et al measured the impact of an after-hours clinic in terms of avoided ED visits and cost savings, and found that 36.8% of patients attending the after-hours clinic would otherwise have gone to the ED if the clinic had not been available [11].…”
Section: Discussionmentioning
confidence: 99%
“…While EDs can re-organize internal procedures to optimize patient flow and delivery of care [8,9], such changes do not stem the ever increasing tide of patients coming to the ED. Redirecting "avoidable" ED visits towards other healthcare services, notably Unscheduled Care Services (UCS), which are alternative clinics that can treat patients with low acuity conditions [10][11][12][13][14][15], is therefore one of the main responses proposed by current reforms [16,17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When these patients are managed appropriately in this setting, literature has shown that benefits include better care for the individual patient and potential cost avoidance for the health-care system at large. [2][3][4] An SRFC model also allows for interprofessional development when other medical specialties become involved. Pharmacy inclusion in the SRFC model offers benefits, such as opportunities to perform community service, educate medical students in pharmacology and pharmacotherapy, and improve patient care and outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Student-run free clinics (SRFCs) deliver care to patients frequently neglected by the health system. [1][2][3] Though SRFC use is associated with decreased ED utilization, 2,3 the drivers of ED use in SRFC patients are poorly described. This study aims to improve our understanding of why SRFC patients visit the ED and generate hypotheses to guide future interventions.…”
Section: Introductionmentioning
confidence: 99%